PENGARUH KOMUNIKASI PEMASARAN DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN DI MIDWAY COFFE KOTA BENGKULU - Vijai Satria; khairul Bahrun (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2023)
The purpose of the study was to determine the effect of marketing communication on product quality on purchasing decisions at Midway Cafe Bengkulu City. This type of research is quantitative research, the method of data collection is done by using observation, documentation and questionnaires. The sample in this study were 65 consumers at Midway CafÃ© Bengkulu City. Analysis of the data used is multiple linear regression test, test of determination and hypothesis testing. Marketing communication has a significant effect on purchasing decisions at Midway Caffe Bengkulu City. Product quality has a significant effect on purchasing decisions at Midway Caffe Bengkulu City. Marketing communication (X1) and product quality (X2) together have a significant effect on purchasing decisions (Y) products at Midway Caffe Bengkulu City. Keywords: Marketing Communication, Product Quality, Purchase Decision